Nekatere značilnosti sodobnega položaja Romov - Klopčič, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2001)
In the contemporary approach to the Roma status throughout Europe, dilemmas and controversies are present, which are reflected mainly in the expressed doubts about the adequacy of the extant manners of expressing the actual interests of the Roma community. Opinions differ most regarding the starting points for the adoption of special measures for the protection of Roma. Can the paternalistic approach on the part of states, reflected in the gradation of protective functions, role of the state and state institutions, possibly beefficient in the prevention of social exclusion, or is this only a way for strengthening the barriers and mutual prejudice between Roma and non-Roma. At the international level, recently a group of intellectually and politicallyinfluential educated Roma, has been formed, that has become an active collocutor of international organizations, striving for the improvementof Roma status. In Slovenia, a number of activities are going on in certain districtsč these are directed towards the improvement of Roma status in the field of education and vocational training. Single examples of good practice in the employment and education of Roma have gradually paved the way for a wider discussion onthe possibilities and modes of dialogue, cooperation, and mutual understanding between Roma and non-Roma population. An integral strategy of the Republic of Slovenia in the shaping of models of education and vocational training for Roma is only being created. The first step in the field of becoming acquainted with the experiences of other states and with international standards has already been made. At the Council of Europe workshop in Novo mesto (October 3-5, 2001) dealing with the improvement of employment possibilities for Roma, experts of the Council of Europe took part together with represenatives of local and state institutions, of the local employment offices, as well as the Roma community of Slovenia.
Keywords: Slovenia; Slovenija; Romi; etnične skupine; pravice manjšin; družbeni položaj; zaposlovanje; education; izobraževanje